Leitura e escrita de crianças com desvio fonológico e de crianças com desenvolvimento fonológico típico - Backes, Fabieli Thaís (2014)
Some skills identified as predictive of the good performance in reading and writing are impaired in children with phonological disorders. Then, this work aims to analyze and compare the performance in reading and writing among children with phonological disorders and children with typical phonological development. Besides, it aims to characterize and differentiate the reading and the writing of both groups of children and verify how the repair strategies, presented in the speech of children with phonological disorders, are reproduced in the mentioned abilities. The data collection was carried out from assessments of reading and writing of isolated words, assessment of reading comprehension and text production. The sample consisted of fifty children, five with phonological disorders - study group - and forty five with typical phonological development - control group. It was applied a descriptive and an inferential statistics to the data. So, it observed a statistically significant difference in relation to the average of the percentage of success in reading and writing of isolated words when comparing the groups. The kind of errors made in reading and writing by the two groups were similar, however, the average of occurrence of these errors was higher in the group of children with phonological disorders, with a statistically significant difference for some errors. In reading comprehension, it was found no difference between the groups, but, in relation to the textual production differences were verified. Finally, for the repair strategies presented in the speech of children with phonological disorders, it was found that in reading the majority was reproduced with a different strategy from that one used in speech, while a minority was produced correctly. However, in terms of writing, the majority was reproduced correctly. Therefore, we conclude that children with phonological disorder showed lower performance in reading and writing of isolated words, as well as in textual production, when compared to children with typical phonological development. It was also noticed some similarities between the groups regarding the kinds of errors in reading and writing of words, however, the average of errors occurrence errors was higher in the group of children with phonological disorders. And, for the repair strategies presented in the speech of children with phonological disorders, it was found that they are not always reproduced in reading and writing.